(untitled) (Bangladesh Journal of Botany, 2021)
Six red sweet pepper genotypes viz., RSPUHF-1, RSPUHF-2, RSPUHF-3, RSPUHF-4, RSPUHF-5 and RSPUHF-7 and their crosses using half-diallel excluding reciprocals were evaluated for combining ability to obtain desired hybrids. Analysis of variance for combining ability revealed that variances due to general combining ability (GCA) and specific combining ability (SCA) were highly significant for all the characters indicating the importance of additive and non-additive gene effects. RSPUHF-3 (‒1.42* and ‒1.5*) and RSPUHF-7 (‒1.25* and ‒1.54*) were found as reliable combiners for earliness and maturity. Whereas, the parents RSPUHF-1 (0.53*, 0.78*, ‒0.5, 0.12*, 0.25*), RSPUHF-2 (1.49*, 2.19*, 6.41*, 0.63*, 2.21*) and RSPUHF-4 (0.69*, 0.9*, 9.92*, 0.47*, 1.28*) were good general combiners for fruit set per cent, number of fruits per plant, fruit weight, fruit yield per plant and fruit yield per m2. Amongst, the crosses, RSPUHF-3 x RSPUHF-2 (0.95*), RSPUHF-4 x RSPUHF-2 (0.77*) and RSPUHF-5 x RSPUHF-2 (0.86*) were found to be the best specific combinations for increased fruit yield and component characters. Further, on the basis of per se performance it may be identified for release after multi location testing the above hybrids have been found to be the most promising for exploitation of heterosis.